2022
DOI: 10.1002/cphc.202200149
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Double Transition Metal Atom Anchored on Graphdiyne Monolayer for Nitrogen Electroreduction

Abstract: Converting N 2 to NH 3 is an essential reaction but remains a great challenge for industries. Developing more efficient catalysts for N 2 reduction under mild conditions is of vital importance. In this work, double transition metal atoms (TM=Mo, W, Nb and Ru) anchored on graphdiyne monolayer (TM 2 @GDY) as electrocatalysts are designed, and the corresponding reaction mechanisms of N 2 electroreduction are systematically investigated by means of first-principles calculations. The results show that the double TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Moreover, many other transition metals (TMs) were also of wide interest to scientists. Recently, it has been reported that Cu, Nb, Mo, Mn, Co, and other transition-metal SACs , (such as Sc, Ti, Zn, etc.) were loaded on GDY.…”
Section: Structure Of Gdy-based Nanostructuresmentioning
confidence: 99%
“…Moreover, many other transition metals (TMs) were also of wide interest to scientists. Recently, it has been reported that Cu, Nb, Mo, Mn, Co, and other transition-metal SACs , (such as Sc, Ti, Zn, etc.) were loaded on GDY.…”
Section: Structure Of Gdy-based Nanostructuresmentioning
confidence: 99%